A study on the classroom learning activities that influence the development of information literacy among senior high school students - Santos, Yhna Therese P. (School of Library and Information Studies, University of the Philippines Diliman, 2011)
The goal of a secondary school is to prepare its students for future education. College education entails far more than the basic research skills needed in high school. Higher-level search strategies and skills are needed to be able to decide which information is valid and which is not. This is why Information Literacy is important for high school students. The skills that enable students to access information effectively, evaluate information accurately and use information creatively enable them to called Information Literate students. In order to create information literate students, teachers must be able to prepare and design classroom learning activities that would develop the information literacy skills of their students. The classroom learning activities designed by the teachers should teach students how to access, evaluate and use information coming from a wide variety of sources.